Pelatihan Pencatatan Keuangan Sederhana dan Mengenalkan Literasi Keuangan Terhadap Siswa SD di Desa Kwasen - Sabilla, Annayya Putri; Audia, Shafa Nissa; Rachma, Emiliana; Adinugraha, Hendri Hermawan; Gunawan, Ade (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The aim of this service activity is to provide training and educate students about the benefits and importance of keeping simple financial records and introducing effective and accurate financial literacy. This service activity uses training methods. Some of them are elementary school students in Kwasen Village, located in Kesesi District, who do not yet understand what cash is and how to apply it because several classes have not yet implemented the cash system. Because of this, simple financial recording training activities were carried out and introduced financial literacy by providing material about the meaning of cash and the function of cash. Participants were asked to listen to the explanation in order to understand the concept of the class cash system. It can be concluded that elementary school children in Kwasen village still do not implement cash records, but they have been taught to save by their parents. So, by carrying out this training, it is hoped that it will be a provision for them in class to implement the treasurer's cash system.